Development of Kampung Chocolate Tourism Destinations in Blitar Regency as Sharia-Based Tourism - Muhammad Sulthon Aziz (PT. Maju Malaqbi Makkarana, 2025)
Based on GMTI 2019 data, it shows that until 2030, the number of Muslim tourists (wislim) is projected to reach 230 million worldwide, and in 2024 as many as 8.5 million tourists. This provides an opportunity for Indonesia to accelerate the development of national halal tourism destinations with global standards for potential destinations, one of which is the Blitar chocolate village. This study aims to determine the development of chocolate village tourist destinations into sharia-based tourist destinations through a qualitative approach, data collected through interviews, and sources from the chocolate village website, observations and documentation, and related subumber sources. Based on the analysis that has been carried out, it can be concluded that the tourist destination of Kampung Chocolate Blitar is an educational tourism by offering 8 kinds of educational packages and family entertainment tours and ecotourism by offering a natural and cultural atmosphere. The measurement of halal tourism in the Blitar chocolate village destination starts from the implementation of tourist destinations that provide benefits and benefits, tourism facilities that are representative and friendly to Muslims as evidenced by CHSE (Cleanliness, Health, Safety, Environment Sustainability) certificates from the Ministry of Tourism and Creative Economy and being a member of the Indonesia Halal in Tourism Association (PPHI), goods and services products have been guaranteed to be halal and avoid disobedience and dishonesty, and the contract applied by susuai is the a'mal contract to employees and the musyarokah and mudhorobah contract to MSME partners and external parties, as well as the ijaroh contract to tourists. From the potential possessed by this chocolate village, the Blitar Chocolate Village destination has great potential to become a sharia-based tourist destination (halal tourism).